2015
DOI: 10.1016/j.atherosclerosis.2015.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Complement proteins and arterial calcification in middle aged women: Cross-sectional effect of cardiovascular fat. The SWAN Cardiovascular Fat Ancillary Study

Abstract: Background CVD risk increases in women after menopause. Recent data suggest higher levels of complement protein C3 and cardiovascular fat (CF) in postmenopausal women. Whether complement proteins are associated with early markers of atherosclerosis in healthy midlife women has never been evaluated. Additionally, the potential impact of the local CF on these associations has never been assessed. Methods Participants (n=100, age (mean(SD)):50.48(2.63), 50% premenopausal) were from the Study of Women's Health A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…For the premenopausal participants, venipuncture was scheduled on days 2–5 of a spontaneous menstrual cycle to evaluate sex hormone levels. For the perimenopausal participants, fasting serum samples were randomly obtained [ 19 ]. Blood samples were drawn after 10 hours of overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…For the premenopausal participants, venipuncture was scheduled on days 2–5 of a spontaneous menstrual cycle to evaluate sex hormone levels. For the perimenopausal participants, fasting serum samples were randomly obtained [ 19 ]. Blood samples were drawn after 10 hours of overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…For the peri-menopausal participants, fasting serum samples were randomly obtained. 62 All investigators successfully completed a training program that was standardized and scripted for all investigators to minimize the interrater variability. Blood samples were collected from all participants between 8:00 AM and 10:00 AM after a minimum of 10-h fasting.…”
Section: Materials and Methods Epidemiological Investigationmentioning
confidence: 99%
“…Activation of the immune response by elevating hydroperoxides levels, further activating NF-kB signaling, may be a key aging feature in the mouse heart [ 38 ]. In addition, Lian et al reported that astroglial NF-kB/C3 activation led to impaired synaptic density and dendritic morphology in brain tissue of Alzheimer’s disease (AD) patients [ 39 ], and the expressions of C3, C4 and C5 mRNA increased with age in C57BL/6 mice brain [ 37 - 39 ]. Here, our proteomic analysis revealed decreased C3 (SP/O: 0.811 and SPD/O: 0.555) and C4 (SP/O: 0.781 and SPD/O: 0.653) expressions in both SP- and SPD-treated rats, which may contribute to the anti-aging effects of these polyamines.…”
Section: Discussionmentioning
confidence: 99%